2020
DOI: 10.1158/1538-7445.sabcs19-gs5-02
|View full text |Cite
|
Sign up to set email alerts
|

Abstract GS5-02: Detection of circulating tumor DNA (ctDNA) after neoadjuvant chemotherapy is significantly associated with disease recurrence in early-stage triple-negative breast cancer (TNBC): Preplanned correlative results from clinical trial BRE12-158

Abstract: Background: A significant proportion of patients with early-stage TNBC are treated with neoadjuvant chemotherapy (NAC). Sequencing of ctDNA after surgery can be used to detect minimal residual disease and predict which patients may experience clinical recurrence. Methods: BRE12-158 is a recently completed Phase II clinical trial which randomized early-stage TNBC patients with residual disease after NAC to post-neoadjuvant genomically-directed therapy vs treatment of physician choice. 151 patients had a plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…ctDNA has been associated with chemotherapy in studies by Riva et al ( 65 ), in which ctDNA-positive patients before and after chemotherapy experienced poor OS and disease-free survival (DFS). Additionally, Radovich et al ( 66 ) reported that patients with early-stage TNBC and positive ctDNA after chemotherapy had a higher risk of disease relapse. Therefore, liquid biopsies are being developed as a non-invasive method to study recurrence, treatment response, and survival in the clinical setting.…”
Section: Circulating Tumor Cells (Ctcs) In Tnbcmentioning
confidence: 99%
“…ctDNA has been associated with chemotherapy in studies by Riva et al ( 65 ), in which ctDNA-positive patients before and after chemotherapy experienced poor OS and disease-free survival (DFS). Additionally, Radovich et al ( 66 ) reported that patients with early-stage TNBC and positive ctDNA after chemotherapy had a higher risk of disease relapse. Therefore, liquid biopsies are being developed as a non-invasive method to study recurrence, treatment response, and survival in the clinical setting.…”
Section: Circulating Tumor Cells (Ctcs) In Tnbcmentioning
confidence: 99%
“…The prognostic significance of ctDNA has also been evaluated during and after NACT for TNBC [ 113 , 114 ]. Riva et al found that ctDNA was positive in 75% of the patients prior to NACT and continued positivity after one cycle of chemotherapy was associated with shorter DFS (p < 0.001) and OS (p = 0.006) [ 113 ].…”
Section: Circulating Tumor Cells and Cell-free Dna As Prognostic Biomarkers In Tnbcmentioning
confidence: 99%
“…Riva et al found that ctDNA was positive in 75% of the patients prior to NACT and continued positivity after one cycle of chemotherapy was associated with shorter DFS (p < 0.001) and OS (p = 0.006) [ 113 ]. Radovich et al found that detection of ctDNA in patients with early-stage TNBC with residual disease after NACT was an independent prognostic risk factor for disease recurrence [ 114 ]. Out of 148 patients, ctDNA was detected in 64% and at a median follow-up of 16.7 months, detection was associated with inferior distant DFS (32.5 mos.…”
Section: Circulating Tumor Cells and Cell-free Dna As Prognostic Biomarkers In Tnbcmentioning
confidence: 99%
“…In a neoadjuvant study, Radovich et al investigated the prognostic significance of CTCs and ctDNA in 196 patients with TNBC and no pathological complete remission (pCR) following the neoadjuvant situation [27]. The clinical follow-up was 17.2 months.…”
Section: "Liquid Biopsy"mentioning
confidence: 99%